Determination and analysis of trace metals and surfactant in air particulate matter during biomass burning haze episode in Malaysia. (September 2016) - Ahmed, Manan; Guo, Xinxin; Zhao, Xing-Min
Abstract: Trace metal species and surface active agent (surfactant) emitted into the atmosphere from natural and anthropogenic source can cause various health related and environmental problems. Limited data exists for determinations of atmospheric particulate matter particularly trace metals and surfactant concentration in Malaysia during biomass burning haze episode. We used simple and validated effective methodology for the determination of trace metals and surfactant in atmospheric particulate matter (TSP & PM2.5 ) collected during the biomass burning haze episode in Kampar, Malaysia from end of August to October 2015. Colorimetric method of analysis was undertaken to determine the concentration of anionic surfactant as methylene blue active substance (MBAS) and cationic surfactant as disulphine blue active substance (DBAS) using a UV–Visible spectrophotometer. Particulate samples were also analyzed for trace metals with inductive coupled plasma mass spectrometer (ICP-MS) followed by extraction from glass microfiber filters with close vessel microwave acid digestion. The result showed that the concentrations of surfactant in both samples (TSP & PM2.5 ) were dominated by MBAS (0.147–4.626 mmol/m 3 ) rather than DBAS (0.111–0.671 mmol/m 3 ) and higher than the other researcher found. Iron (147.31–1381.19 μg/m 3 ) was recorded leading trace metal in PM followed by Al, Zn, Pb, Cd, Cr and others. During the haze period the highest mass concentration of TSP 313.34 μg/m 3 and 191.07 μg/m 3 for PM2.5 were recorded. Furthermore, the backward air trajectories from Kampar in north of peninsular Malaysia confirmed that nearly all the winds paths originate from Sumatera and Kalimantan, Indonesia. Highlights: Atmospheric particulate matter investigation particularly surfactant and trace metals from biomass burning. Two types of particulate sample (TSP + PM2.5 ) were collected. A cost effective and simple method used for analysis. Air mass backward trajectories analysis used to identify the source of PM.